BIR SO‘Z TURKUMIDAGI OMONIM SO‘ZLARNI ANIQLASH USULLARI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
One of the important tasks in the field of natural language processing is the issue of homonymy. This problem exists in different natural languages, and different methods are proposed in each natural language. Different methods can be used for semantic differentiation of homonyms. In the semantic differentiation of homonymous words in the Uzbek language, different methods can be used depending on whether they meet in different word groups and within the same word group. This article discusses the methods of semantic differentiation of homonyms within the same word group. The world experiences of using the methods of the Machine Learning approach in determining homonymy within a word group were studied.
Keywords: NLP (natural language processing), homonymy, Machine learning approach, context, word sense disambiguation (WSD-word sense disambiguation)